2005
DOI: 10.1007/s10681-005-3157-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between common wheat (Triticum aestivum L.) gluten proteins and dough rheological properties

Abstract: This paper reports the correlation between the rheological properties of bread wheat dough and the types and quantities of endosperm proteins in 28 common wheat cultivars. Different methods were used to analyse the allelic composition of these cultivars and the relative quantities of the different proteins contributing to the gluten structure. Neither dough strength (W) nor tenacity/extensibility (P/L) correlated with allelic composition. Different wheats with the same allelic composition (i.e., with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…Oury et al (2010) also reported that 1 and 2* subunits had no significant effects on alveograph parameters and baking properties. However, these subunits were associated with a higher loaf volume compared to the Null subunit (Peña et al 2005;Vázquez et al 2012). Glu-B1 alleles had an effect on SV (p < 0.05).…”
Section: Baking Qualitymentioning
confidence: 91%
See 2 more Smart Citations
“…Oury et al (2010) also reported that 1 and 2* subunits had no significant effects on alveograph parameters and baking properties. However, these subunits were associated with a higher loaf volume compared to the Null subunit (Peña et al 2005;Vázquez et al 2012). Glu-B1 alleles had an effect on SV (p < 0.05).…”
Section: Baking Qualitymentioning
confidence: 91%
“…The flours containing 5+10 subunits, which are associated with good baking quality (Peña et al 2005;Vázquez et al 2012), had higher RE, higher SV, and lower BF (Table 5). …”
Section: Baking Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The allelic variation at HMW-GS and LMW-GS and environmental conditions are important factors that influence the wheat flour quality parameters (Branlard et al, 2003;(Knežević et al, 2017b). Alleles (a, b) encoded at the Glu-A1 were associated with a higher loaf volume compared to the Null subunit (c), and allele Glu-D1d encoding 5+10 associated with good baking quality (Peña et al 2005;Vázquez et al 2012). However Glu-B1c encoding 7+9 subunits are associated with low baking quality, whereas i and b allele encoding 17+18 and 7+8 subunits are associated with good baking characteristics (Menkovska et al, 2002;Liang et al (2010).…”
Section: Resultsmentioning
confidence: 97%
“…The gluten composes about 80% of the protein fraction of wheat grain endosperm, consisting of subunits of glutenins and gliadins (Peña et al, 2002;. Glutenins give tenacity to the dough while gliadins are responsible for extensibility (Peña et al, 2005). Of these two fractions, glutenin is the main responsible for the gluten strength (Peña et al, 2002).…”
Section: Resultsmentioning
confidence: 99%